2004
DOI: 10.1111/j.1582-4934.2004.tb00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding affinities for sulfonamide inhibitors with matrix metalloproteinase‐2 using a linear response method

Abstract: The extracellular matrix (ECM) is a complex structural entity surrounding and supporting cells that are found within mammalian tissues. It is composed of three major classes of biomolecules: (i) structural proteins: collagen and elastin, (ii) specialized proteins: e.g. fibrillin, fibronectin, and laminin, and (iii) proteoglycans.Matrix metalloproteinases (MMPs) are an important class of calcium dependent zinc-containing endopeptidases, involved in the breakdown of ECM, thus playing important roles in growth, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Including Coulombic interactions beyond the sphere of hydration introduces vacuum-like electric fields into the system which are not properly screened by solvent, leading to a number of artefacts [79,124]. Partial pragmatic remedies to these issues may include selective neutralisation of the receptor titratable groups and/or use of continuum models to correct the ∆<V elec_Lig > term for long-range electrostatics [113,123,124,263,279,283,285]. On the other hand, several studies yielded operational LIE models without reported ad hoc adjustment of the system charges [106,107,[286][287][288].…”
Section: The Lie Approach: Methods and Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Including Coulombic interactions beyond the sphere of hydration introduces vacuum-like electric fields into the system which are not properly screened by solvent, leading to a number of artefacts [79,124]. Partial pragmatic remedies to these issues may include selective neutralisation of the receptor titratable groups and/or use of continuum models to correct the ∆<V elec_Lig > term for long-range electrostatics [113,123,124,263,279,283,285]. On the other hand, several studies yielded operational LIE models without reported ad hoc adjustment of the system charges [106,107,[286][287][288].…”
Section: The Lie Approach: Methods and Applicationsmentioning
confidence: 99%
“…For the unbound ligand the Coulombic and van der Waals interactions are zero because the solvent is represented by a continuum, while in the bound state these interactions are computed between ligand and receptor. The continuum model can be used in conjunction with MD, MC or hybrid MD/MC (HMC) protocols [112,113], or energy minimization only [113,279,294,297]. A variation is to apply the continuum model after conformational sampling of the ligand-receptor in vacuo, without simulating the free ligand [281].…”
Section: The Lie Approach: Methods and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not entirely unexpected given a variety of preclinical studies that indicate that MMP inhibitors work effectively in early-stage cancer and not in the terminal ones. Our group is also interested in the in silico study of MMPs -synthetic MMP inhibitors interactions [11].…”
mentioning
confidence: 99%